Environmental factors associated with cheatgrass invasion in the Gunnison Basin, Colorado - Sokolow, Shannon, author; Leininger, Wayne, advisor; Brummer, Joe E., advisor; Barbarick, K. A., committee member; Milchunas, Daniel G., committee member (Colorado State University. Libraries, 2005)
Cheatgrass (Bromus tectorum L.) has invaded vast areas of sagebrush (Artemisia tridentata Nutt.) dominated rangeland throughout the western U.S. In the high-elevation, semi-desert, sagebrush ecosystem of the Gunnison Basin, cheatgrass infestations are primarily restricted to disturbed sites. I conducted observational and experimental studies to evaluate: 1) the range of a viable seedbank from the edge of cheatgrass patches into the native communities, 2) the differences in soil characteristics under the cheatgrass invaded and uninvaded communities, and 3) the effects of surface soil disturbance, addition of shredded sagebrush litter, and addition of water to simulate above-normal fall precipitation on cheatgrass establishment and productivity. Results of the observational studies suggest that there are viable cheatgrass seeds up to 2 m into the uninvaded areas of the Gunnison Basin, but for some unknown reason, they do not germinate and/or successfully establish. I observed significantly higher nitrate-nitrogen in invaded areas once the cheatgrass senesced, strong trends towards lower soil organic matter, total organic carbon, total carbon and total nitrogen in the invaded areas, and significantly higher phosphorus-to-iron ratios in cheatgrass invaded areas compared to uninvaded areas. Results of the observational studies suggest that there are likely a variety of interacting environmental conditions that could be preventing the germination or establishment of cheatgrass seeds outside of the cheatgrass patches. Results of my experimental study suggest that land management tools that disturb surface soil or add litter may increase the invasibility of cheatgrass into high-elevation, sagebrush habitats in the Gunnison Basin. There was no significant effect of adding additional water on cheatgrass density, biomass, or seed density, which might have been attributed to the above-normal precipitation (about 2.5 times > 30 year average) that naturally occurred in September 2003 (the water treatment application period). Plots under the sagebrush plants had significantly higher cheatgrass density, biomass, and seed density than interspace plots. In both plot locations, disturbance significantly increased cheatgrass density, biomass, and seed density. Similarly, adding sagebrush litter in interspaces significantly increased cheatgrass density, biomass, and seed density compared to the controls. Despite the significant soil treatment effects and the natural, above-normal precipitation that occurred, the small amount of cheatgrass biomass and seed produced during this study indicates that cheatgrass in the Gunnison Basin is kept in check by a variety of environmental factors.
Keywords: Cheatgrass brome -- Colorado -- Gunnison River Watershed; Invasive plants -- Colorado -- Gunnison River Watershed